(untitled) (Medical Forum Monthly, 2024)
ABSTRACT Objective: To observe the gross anatomical changes of the stomach and the changes in the body weight in albino rats after oral administration of ibuprofen and L-Arginine Study Design: A prospective experimental study. Place and Duration of Study: This study was conducted at the Department of Anatomy, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre Karachi from 01.04.2008 to 31.7.2008 Materials and Methods: For this study 45 albino rats of either sex between 90-120 days were taken and divided into three Groups, ‘A’, ‘B’ and ‘C’, containing 15 animals each, which were further sub-divided into three sub-groups containing 5 animals each according to the time of sacrifice, i.e. 4, 6, and 8 weeks respectively. Group ‘A’ served as control. Group ‘B’ received ibuprofen at the dose of 70 mg per kilogram body weight per day with feed and Group ‘C’ received ibuprofen at the dose of 70 mg per kilogram body weight per day with feed and L-Arginine300 mg per kilogram body weight per day with feed. Animals were weighed on Sartorius balance before and after their stipulated time period and then were fixed on a dissecting board, the abdomen was opened with a long midline incision and the stomach was removed and observed for gross anatomical changes. Stomach wasthen opened along the greater curvature with an incision extending from cardiac to the pyloric end.After removing the contents of the stomach the gastric mucosa was examined by dissecting microscope. Results: The animals of Group ‘A’ were healthy and active. On gross examination no abnormality was detected. The animals of Group ‘B’ were weak, sluggish in activities.Their food intake was decreased when compared to control. The gross observation of the external surface of stomach was dull, slightly red and blood vessels were dilated in all subgroups. Under the dissecting microscope the mucosa was red, swollen and erosions were observed in all subgroups. There was a decrease in the final body weight of animals. In subgroup B1 it was moderately significant (P<0.01) and in case of B2 and B3 this decrease was significant (P<0.05) when compared to control. The animals in group C were looking healthy and active at the time of sacrifice.On gross examination of stomach, the surface appeared smooth, shiny and few blood vessels were observed. The mucosal surface was greyish in the cardiac part and pink in the body and pyloric part. Under the dissecting microscope, few blood vessels were observed. Conclusion: Present study concludes that the long term use of ibuprofen can cause gastric mucosal changes and decrease in body weight in albino rats. L-Arginine supplementation can ameliorate the changes.